POLITICS, ACTIVISM AND TROLLING ON THE RUSSIAN INTERNET - Miazhevich, Galina; Wijermars, Mariëlle; Gapova, Elena; Zvereva, Vera (AoIR Selected Papers of Internet Research, 2018)
In the years that have passed since the social media powered protest movement of 2011-2012, the Russian government has dramatically expanded its restrictions on the Internet, while simultaneously consolidating its grip on traditional media. The Internet, which long provided a space for alternative media and free speech to blossom, is becoming increasingly restricted by a growing corpus of legislation and expanding state surveillance. With legally ill-defined prohibitions on, e.g., offending the feelings of religious believers, propagating 'non-traditional family values' and disseminating 'extremism' in place, online freedom of speech in Russia is at threat. Meanwhile, the Russian state continues to refine its skills in covertly manipulating online discourses, as it has quite successfully practiced it since the 2000s. Yet, because of its transnational configuration, the Internet continues to evade comprehensive state control and offers ever new opportunities for disseminating and consuming dissenting opinions. Developments over the past year, including the series of anti-corruption mass protests organised by opposition leader Aleksei Navalny's Anti-Corruption Foundation, have demonstrated how online challenges to the status-quo are still able to gather momentum and create 'real world' political turbulence. The panel presents a multifaceted investigation of how the Russian-language segment of the Internet, often dubbed Runet, is shaped by and gives shape to online politics and activism. How should we understand the particular complexities of these contestations between an increasingly authoritarian state and its citizens? How are these processes facilitated or hampered by the infrastructural conditions created by national and global media industries and internet companies?